On joint mobility design in multi-structural systems. (May 2016) - Lee, Dooho; Kim, Yong-Dae; Lee, Nam-Young; Lee, Sang-Woo
This article aims to develop a measure that can estimate the isolator performance in joint design problems. The relationships between the receptances of the connection points and the isolator bushes in multi-structural car-body systems are explored from the perspective of a frequency-response-function-based substructuring method. From the formulation for the frequency-response-function-based substructuring method, the desirable magnitude difference between the receptances is proposed through an order analysis of a one-dimensional system. The receptance magnitude concept is extended to a multi-structural system using a singular-value diagram. In order to represent the magnitude of the receptance matrices, matrix measures are introduced. Using the defined measures, a joint design index is proposed in order to assess the structural joint system which consists of two structures and isolator bushes. Finally, two numerical examples are used to demonstrate the relationships between the suggested joint design concept and the relevant responses (i.e. the vibrations, the force and the power) of the structures. The proposed joint design index can estimate the isolator performance and indicate the possibilities for improvement in multi-structural systems, which is very useful for noise and vibration reduction in the automotive industry.